Improv for writers : 10 secrets to help novelists and screenwriters bypass writer's block and generate infinite ideas - Marie, Jorjeana (Ten Speed Press, 2019)
"Improv instructor and writer Jorjeana Marie presents the first book to harness the creative power of improvisation exercises to help both aspiring and seasoned authors defeat writer's block and generate new ideas"--